2020
DOI: 10.3390/ijerph17103439
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict the Evolution of Depressive Symptoms, Adjustment, and Perceived Social Support of Pregnant Women from Their Personality Characteristics? a Technology-Supported Longitudinal Study

Abstract: Background: Research exploring the relationship between personality and important pregnancy outcomes (i.e., depressive symptoms, adjustment, and perceived social support) tends to be cross-sectional, arguably due to the difficulties of conducting longitudinal and mental health research in this population. The objective of this study is to use a web-based solution to longitudinally explore how personality traits are associated, not only with the co-occurrence of these outcomes but also with their evolution duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…In addition to allowing the collection of patients’ pain-related data in an automated way, the results of this study were suggestive of the effectiveness of telemonitoring in pain and other mental health outcomes (e.g., depressive symptoms), particularly if an alarm system that allow changes in pain management can be implemented. Andreu-Pejó et al [ 12 ] examined a sample of 85 pregnant women who participated in a web-based platform HappyMom (Mamáfeliz), which longitudinally assessed a set of risk factors for the development of perinatal emotional disorders. The results showed that certain personality characteristics (e.g., high neuroticism) may be a risk factor to pregnant women’s wellbeing deterioration and therefore should be assessed early during pregnancy mental health screening, which might be facilitated through the use of ICT tools.…”
mentioning
confidence: 99%
“…In addition to allowing the collection of patients’ pain-related data in an automated way, the results of this study were suggestive of the effectiveness of telemonitoring in pain and other mental health outcomes (e.g., depressive symptoms), particularly if an alarm system that allow changes in pain management can be implemented. Andreu-Pejó et al [ 12 ] examined a sample of 85 pregnant women who participated in a web-based platform HappyMom (Mamáfeliz), which longitudinally assessed a set of risk factors for the development of perinatal emotional disorders. The results showed that certain personality characteristics (e.g., high neuroticism) may be a risk factor to pregnant women’s wellbeing deterioration and therefore should be assessed early during pregnancy mental health screening, which might be facilitated through the use of ICT tools.…”
mentioning
confidence: 99%
“…In terms of the factors influencing depression and anxiety symptoms during pregnancy, negative experiences and environmental factors such as childhood abuse, general life stress, unplanned pregnancy, and being a single mother have received great attention in the literature ( 13 15 ). In addition to these factors, recent research has indicated the need to explore the relationship between personality characteristics and emotional distress in pregnancy ( 13 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…A survey in China also reported that both high psychoticism and neuroticism personality characteristics are risk factors for depressive symptoms among Chinese pregnant women ( 17 ). A recent study in 85 pregnant women reported that psychoticism, neuroticism, and low extraversion were all cross-sectionally and longitudinally linked to depression symptoms ( 16 ). These limited empirical studies with relatively small samples indicated that the personality characteristics of pregnant women are closely associated with emotional distress and that pregnant women with high levels of neuroticism and psychoticism, as well as low levels of extraversion, might be more likely to experience depressive and/or anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also know that online interventions do not negatively affect the therapeutic relationship [ 28 ] and that the users generally show high levels of acceptance and satisfaction with this delivery format [ 29 ]. The use of Information and Communication Technologies (ICTs) reduces the burden on health professionals and users, facilitating data collection and accessibility to Treatment [ 30 ]. In fact, different studies have shown the need to develop technology-based interventions to increase accessibility to treatment for BS candidates because their obesity condition significantly affects their mobility, and that makes it difficult for them to attend weekly sessions on-site [ 31 ].…”
Section: Introductionmentioning
confidence: 99%